Anti-Maori themes in New Zealand journalism–toward alternative practice - Moewaka Barnes, Angela; Borell, Belinda; Taiapa, Ken; Rankine, Jenny; Nairn, Ray; McCreanor, Tim (Pacific Journalism Review, 2012)
Gale Academic OneFile includes Anti-Maori themes in New Zealand journalism–toward alt by Angela Moewaka Barnes, Belinda Borell, . Click to explore.
Keywords: health; media; privilege; racism; representation; wellbeing

Suburban Newspapers’ reporting of Māori news - Rankine, Jenny; Moewaka Barnes, Angela; Borell, Belinda; McCreanor, Tim; Nairn, Raymond; Gregory, Amanda (Pacific Journalism Review : Te Koakoa, 2011)
A content analysis of editorial items about Māori issues and the Treaty of Waitangi in 14 Suburban Newspaper publications in Auckland and Northland found a low proportion of articles about these issues, despite high proportions of Māori resident in several areas served by these publications. Stories included a higher proportion of apparent news releases compared to a national sample of non-daily papers. Māori perspectives came largely from sources representing pan-Māori non-government organisations; Suburban Newspapers used a low proportion of iwi and hapū sources compared with other community papers. Use of te reo Māori was low, and there were no signs of attempts to support readers in learning or increasing their understanding of te reo Māori. This article concludes that Māori and non-Māori readers are poorly served by the poverty of Suburban Newspapers’ reporting of Treaty and Māori issues.
Keywords: media; representation; te reo māori

Media & Te Tiriti o Waitangi 2004 - Moewaka Barnes, Angela; Gregory, Mandi; McCreanor, Timothy; Nairn, Raymond; Pega, Frank; Rankine, Jenny (Kupu Taea, Media and Te Tiriti Project, 2005)
Keywords: iwi taketake; journalism; mass media and race relations; media; tiriti o waitangi/treaty of waitangi